THE RELATIONSHIP BETWEEN EMOTIONAL DISORDERS AND EATING BEHAVIOUR IN ADULTS UNDER MARTIAL LAW - Lytvynenko, Olena; Boiko, Polina (Personality and environmental issues, 2026)
The article is devoted to a comprehensive theoretical and empirical analysis of the relationship between emotional disturbances and eating behavior in adults under conditions of martial law. The relevance of the study is determined by the prolonged impact of war-related stress on the psycho-emotional state of the population and the increased risk of maladaptive behavioral patterns, particularly in the domain of eating behavior. The paper analyzes scientific approaches to the understanding of the concepts of emotional disturbances and eating behavior, outlines their main types, psychological mechanisms of formation, and specific features of manifestation in adulthood under conditions of chronic stress and traumatic events.To achieve the research objectives, a combination of theoretical methods (analysis, generalization, and systematization of contemporary psychological literature) and psychodiagnostic tools aimed at assessing key emotional states and behavioral changes was employed. The study used the Beck Anxiety Inventory (BAI), the Patient Health Questionnaire (PHQ-9), the Impact of Event Scale (D. Weiss, C. Marmar), as well as an author-designed questionnaire focused on identifying features of eating behavior and changes in body weight under wartime conditions.The empirical findings indicate that a significant proportion of respondents demonstrate elevated levels of depression and anxiety, reflecting a high degree of emotional distress associated with exposure to war-related events. At the same time, no direct statistically significant relationship was found between the level of emotional disturbances and changes in body weight. However, respondents who exhibited a tendency toward suicidal behavior were more likely to experience weight fluctuations and pronounced changes in eating habits.The obtained data suggest a complex and mediated relationship between emotional disturbances, eating behavior, and body weight. Further research with larger samples, the application of objective assessment methods, and a longitudinal design is required to deepen the understanding of these relationships and to develop effective psychopreventive and corrective interventions.